An inquiry into the University of the Philippines graduate students' learning expectations - Baltazar, Cesar P. (2008)
The study investigated the learning expectations of UP graduate students in each of four learning preferences-Formal Education, Open Education, Mentoring, and Community Learning-in the ecology of learning. Narrative inquiry was primarily used, supported by the survey quesionnaire and focus group discussion. The sample was composed of 300 students from UP College of Education, UP College of Engineering, and the UP College of Arts and Letters. Results showed that achieving lifelong competencies in the four learning preferences was critical in the learning process. Finally, learning expectations of UP graduate students under the learning preferences were seen to be in a dynamic condition.